RESOLUSI KONFLIK AGRARIA DI KABUPATEN LEBONG DALAM PERSPEKTIF FACE NEGOTATION THEORY - Puji Haryadi Mulyana Sukma; Panji Suminar; Dhanurseto Hadiprashada (Syntax Literate, 2023)
Agrarian conflicts related to forest areas also occurred in Lebong Regency, Bengkulu Province, namely the Tes Lake Natural Tourism Park Forest area. Area designation Nature Tourism Park Lake Tes has an impact on the community because they cannot take care of certificates or the legality of land ownership in the area even though the community has lived there before the issuance of the zoning regulations Nature Tourism Park Tes Lake. This study aims to understand and explain conflict resolution Nature Tourism Park Tes Lake in perspective Face Negotation Theory. This research uses a qualitative approach with a case study research type and is descriptive in nature. The results of this study found that the conflict actors Nature Tourism Park Tes Lake involves the community and the Ministry of Environment and Forestry. The conflict resolution is carried out by teamwork in the Agrarian Reform Task Force and analysed through Face Negotiation Theory. The team involved in conflict resolution Nature Tourism Park Lake of Tests did not practice evasion but had a sense of responsibility for resolving conflicts Nature Tourism Park Lake Tes, according to their respective duties, compromises and integrates with each other to resolve conflicts Nature Tourism Park Tes Lake.